Influence of Alkali Treatment and Maleated Polypropylene (MAPP) Compatibilizer on the Dry-Sliding Wear and Frictional Behavior of Borassus Fruit Fine Fiber (BFF)/Polypropylene (PP) Polymer Composites for Various Engineering Applications - Sumit Nijjar; P. Sudhakara; Shubham Sharma; Sanjeev Saini; Aklilu Teklemariam; V. Mariselvam; Satheesh Kumar Sampath; J. I. Song (Advances in Materials Science and Engineering)
Tribological properties of the novel Borassus fruit fine fiber- (BFF-) reinforced polypropylene (PP) composites with respect to fiber matrix surface modifications have been described. Composites were fabricated by an injection molding process using Borassus fruit fine fiber (BFF) of 5 wt.% as reinforcement and polypropylene (PP) as a matrix component. Fibers were treated with alkali (T) to remove the residual lignin (if present) and to enhance the interfacial adhesion between the fiber/matrix interface. Alkali treatment reveals additional reactive functional groups here on the surface of the Borassus fiber, allowing effective interaction bonding with the polypropylene matrix. Borassus fibers are primarily treated with an alkali solution to extract weaker unstructured amorphous constituents so that the fibers retain crystallized components, thereby strengthening the fiber’s strength. A 5 wt.% of maleated polypropylene (MAPP) was used as a compatibilizer to improve the interfacial adhesion between fiber and the polymer matrix. The wear and frictional behavior of BFF/PP composites with respect to the modifications were evaluated by steel counterface utilizing pin-on-disc test contraption under dry-sliding conditions. The sliding velocity, applied load, and sliding distance were maintained as 2.198 m/s, 9.81–29.43 N, and 4000 m, respectively. The results demonstrate that the reinforcement of BFF to polypropylene matrix and the modifications improved the wear properties of the neat polymer matrix. Findings concluded that the abrasive wear resistance of T + PP + MAPP composite showed better interfacial adhesion and bonding, thus resulting in better tribological performance as compared to the other three compositions under different loading conditions. The effective substantial improvement of the coefficient of friction has been observed in alkali-treated fiber and polypropylene matrix with MAPP compatibilizer (T + PP + MAPP) composites due to the presence of MAPP compatibilizer and alkali-treated fibers. The frictional coefficient of T + PP + MAPP possesses better interfacial bonding strength upon NaOH treatment, and coupling agent, which results in enhancement of effective contact surface area and good surface friction characteristics, has been observed under different loading conditions. The fracture mechanism of worn-out portions of BFF/PP composites was studied using high-resolution scanning electron microscopy to analyze various imperfections like debonding, splits, fiber cracks, and wreckage or fragments formation.